Reconstructing Islamic Character Education Through Islamic Religious Education: A Critical Literature Review - Lutfi Rachman (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
This study critically examines and reconceptualizes the role of Islamic Religious Education (Pendidikan Agama Islam/PAI) in strengthening Islamic character (akhlaq) among students in Indonesian educational institutions. Employing a qualitative library research methodology grounded in systematic content analysis, the study draws upon classical Islamic educational theory, contemporary pedagogical literature, and national education policy frameworks. The findings reveal that PAI functions as a strategic instrument of moral, spiritual, and social formation through three interconnected pillars: integration of moral values (akhlaq) into curriculum design, teacher role modeling (uswah hasanah), and value-based contextual learning. The reconstruction of Islamic character education demands synergy among school, family, and community as a holistic value-education ecosystem. This article argues that PAI transcends mere transmission of religious knowledge to become a transformative process of forming students who are faithful (iman), pious (taqwa), and morally excellent (akhlaq al-karimah), fully aligned with the national education vision and the Islamic principle of rahmatan lil ‘alamin. Grounded in the classical thought of al-Ghazali, Ibn Miskawaih, and Ibn Sina, as well as contemporary scholars, this study offers a three-dimensional conceptual model philosophical, pedagogical, and sociological as a framework for PAI-based character strengthening in the modern educational context.